Math, asked by jubinjoy432ou61r2, 1 year ago

Please answer this question from trignometry



Attachments:

Answers

Answered by AR17
2
Heya user !!!

Here's the answer you are looking for

SinA = mSinB

m/SinA = 1/SinB

As 1/Sinθ = Cosecθ

So, CosecB = m/SinA --------------1

Similarly,

TanA = nTanB

1/TanB = n/TanA

As Cotθ = 1/Tanθ

Therefore, CotB = n/TanA ---------------2

We know,

Cosec^2θ - Cot^2θ = 1

Thus, Cosec^2B - Cot^2B = 1

Substituting the value of CosecB and CotB from equation 1 and equation 2

(m/SinA)^2 - (n/TanA)^2 = 1

m^2/Sin^2A - n^2 Cos^2A/Sin^2A = 1 (As Tan^2A = Sin^2A/Cos^2A)

m^2 - n^2 Cos^2A = Sin^2A

m^2 - n^2 Cos^2A = 1 - Cos^2A (Sin^2A = 1 - Cos^2A)

n^2Cos^2A - Cos^2A = m^2 - 1

Cos^2A (n^2 - 1) = m^2 - 1

Cos^2A = (m^2 - 1) / (n^2 - 1)


★★ HOPE THAT HELPS ☺️ ★★

jubinjoy432ou61r2: Is there any other way to prove it?If there is ,please tell me.
AR17: i got only this way.... sry...
Answered by Riya1045
0

Answer:

We value your trust. In order to honour that trust, BYJU'S adheres to ethical standards in gathering, using, and safeguarding any information you provide. Think and Learn Private Limited (operating under the brandname BYJU'S), is a leading edtech company, incorporated in India, for imparting learning. This privacy policy governs your use of the application 'BYJU's - The Learning App' ('Application'), www. Byju's.com ('Website') and the other associated applications, products, websites and services managed by the Company. Please read this privacy policy ('Policy') carefully before using the Application, Website, our services and products, along with the Terms of Use ('ToU') provided on the Application and the Website. Your use of the Website, Application, or services in connection with the Application

Similar questions